Implications of VAT Increase and Global Price Volatility on Middle Class Consumption Behavior and Urban Inflation Rate in Central Java - Hardiwinoto, Hardiwinoto; Lasmiatun, KMT; Arini, Rani Eka (West Science Social and Humanities Studies, 2025)
This study examines the implications of VAT increases and global price volatility on middle-class consumption behavior and the urban inflation rate in West Java. Using a quantitative approach, data from 200 respondents were analyzed via Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results reveal that VAT increases significantly influence both middle-class consumption patterns and urban inflation, with stronger effects compared to global price volatility. VAT adjustments impact household spending priorities and contribute to inflationary pressures in urban areas, while global price fluctuations moderately affect consumption behavior and inflation through external market dependencies. These findings underscore the need for balanced fiscal policies and strategies to manage external economic shocks to ensure urban economic stability and resilience.